(untitled) (Transport systems and technologies, 2020)
Traffic safety is a crucial requirement for the operation of railways. Rail crashes have the greatest risk of derailment, with serious consequences. According to the results of the analysis, the consequences of the east are serious damage to the rolling stock, railway tracks and other elements of the railway infrastructure, slowing down and disruption of the train schedule. A significant drawback of railway transport is the restriction of the speed of trains with light-duty freight cars in the empty state, equipped with carts model 18-100. Among the reasons for the rise of the wheels of the wagons from the rails associated with the malfunctions of the undercarriage of the wagons, the following can be called: breakage of the side frames and cantilever beams of carts, breakage of axles and wheels, malfunctions of roller bearings of the axle assembly, wear of elements of friction dampers oscillations and bodies on the beam beams, the deviations of the sizes of the carts are inadmissible. Another important reason is the negative reduction of the wagon container by more than 10% of the factory installed by the factory. These faults, in particular those associated with the destruction of the undercarriage elements, directly lead to the descent of the wagons. However, some of them do not directly cause sunrise, but are the causes of the development of dynamic processes that cause increased force interaction of the rolling stock.